Explanatory factors of dynamic balance impairment in myotonic dystrophy type 1. Issue 6 (14th March 2022) - Bélair, Nicolas; Côté, Isabelle; Gagnon, Cynthia; Mathieu, Jean; Duchesne, Elise
Abstract: Introduction/Aims: Myotonic dystrophy type 1 (DM1) is a neuromuscular disease affecting many systems and for which muscle weakness is one of the cardinal symptoms. People with DM1 also present with balance‐related impairments and high fall risk. The aim of this study was to explore explanatory factors of dynamic balance impairment in the DM1 population. Methods: A secondary analysis of data collected as part of a larger study was performed. The Mini Balance Evaluation System Test (Mini‐BESTest) was used to assess dynamic balance. Age, sex, and CTG repeat length in blood were retrieved from medical records and research files. The maximal isometric muscle strength of five lower limb muscle groups (hip flexors and extensors, knee flexors and extensors, and ankle dorsiflexors) was quantitatively assessed as well as fatigue. Standard multiple regression analysis was used. Results: Fifty‐two individuals (31 men) aged between 24 and 81 years were included. The final model explains 65.9% of the balance score; ankle dorsiflexor muscle strength was the strongest explanatory factor, followed by CTG repeat length, age and fatigue to a lesser extent. Discussion: Dynamic balance is impaired in people with DM1. Results of this study suggest that rehabilitation interventions aimed at improving strength of the ankle dorsiflexors and managing fatigue could help to improve dynamic balance in this specific population.